THE INFLUENCE OF LIQUIDITY (CR), PROFITABILITY (ROA), CAPITAL STRUCTURE (DAR), AND INTELLECTUAL CAPITAL (VAIC) TOWARD EARNINGS QUALITY ON INDUSTRIAL SECTOR COMPANIES THAT LISTED ON INDONESIA STOCK EXCHANGE FROM 2018-2022 - Hadi, Syukri; CH, Stephen Setiahady; Fadrul, Fadrul; Hadi, M. Fikry (Bilancia : Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the influence of Liquidity, Profitability, Capital Structure and Intellectual Capital on the Quality of Profits in Industrial Sector Companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research uses secondary data. The sampling technique used in this research was purposive sampling and the number of samples obtained was 28 companies. The research method used is a multiple regression analysis technique using the SmartPLS4.0 software. The results of this research show that only the Capital Structure variable has a significant influence on Earnings Quality. Meanwhile, for the remainder, Liquidity, Profitability and Intellectual Capital do not have a significant influence on Earnings Quality. Keywords: Quality of Earnings; Liquidity; Profitability; Capital Structure; Intellectual Capital ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh Likuiditas, Profitabilitas, Struktur Modal, dan Modal Intelektual terhadap Kualitas Laba pada Perusahaan Sektor Perindustrian yang terdaftar di Bursa Efek Indonesia periode 2018-2022. Penelitian ini menggunakan data sekunder. Teknik pengambilan sampel yang digunakan pada penelitian ini adalah purposive sampling dan jumlah sampel yang diperoleh sebanyak 28 perusahaan. Metode penelitian yang digunakan adalah teknik analisis regresi berganda dengan menggunakan bantuan software SmartPLS 4.0. Hasil dari penelitian ini menunjukkan bahwa hanya variabel Struktur Modal yang memiliki pengaruh signifikan terhadap Kualitas Laba. Sedangkan sisanya, Likuiditas, Profitabilitas, dan Modal Intelektual tidak memiliki pengaruh yang signifikan terhadap Kualitas Laba. Kata Kunci : Earnings Quality; Liquidity; Profitability; Capital Structure; Intellectual Capital